A Bibliometric Analysis of the Development of Research on Environmental Issues and Sustainability in Modern Society's Built Environment Studies in Indonesia - Loso Judijanto; Arief Fahmi Lubis; Ja'far Amir; Nanda Hidayati (Westscience Press, 2023)
This bibliometric analysis delves into the landscape of environmental sustainability research within Indonesia's built environment studies. As a nation undergoing rapid urbanization, understanding the trajectory of scholarly contributions addressing environmental issues becomes imperative. The study employs comprehensive data metrics, including publication trends, influential works, and potential research gaps, to offer a panoramic view of the field. Through clustering and overlay visualization, research trends are identified, and the top-cited documents shed light on influential works. The analysis also reveals less-explored areas, guiding future research directions. The comparison with previous studies enriches our understanding of the field's evolution. The implications extend beyond academia, providing practical guidance for policymakers and practitioners involved in shaping Indonesia's built environment sustainably.